Absolute configuration of the diastereomers of adenosine 5'-O-(1-thiotriphosphate): consequences for the stereochemistry of polymerization by DNA-dependent RNA polymerase from Escherichia coli. - Burgers, P M (1978)
The diastereomers of uridyl-(3'-5')adenyl-O,O-phosphorothioate [Up(S)A] have been separated by high-performance liquid chromatography. Their identification as RP and SP follows from the RNase A digestion of these products. It was then shown, by the same method, that the R isomer is hydrolyzed by snake venom phosphodiesterase (PDEase) approximately 500 times faster than the S isomer. Similarly, the stereoisomer of adenosine 5'-O-(1-thiotriphosphate) (ATPalphaS), until now arbitrarily designated as isomer B, is hydrolyzed ca 400 times faster by PDEase than is isomer A. From these results it is concluded that the R isomers of Up(S)A and ATPalphaS, isomers B, have the same absolute configuration. It then follows that isomer A of ATPalphaS, the preferred of the two isomers as substrate for DNA-dependent RNA polymerase, has the S configuration. The implications for the stereochemistry of action of the latter enzyme are discussed.